Low-smoke flame-retardant TPE composite material and preparation method thereof

By using organic-inorganic co-effect flame retardant prepared by using halogen-free flame retardant elements such as nitrogen, phosphorus, silicon and magnesium hydroxide, the problems of thick smoke and toxic gases during combustion of TPE composites are solved, and efficient and safe resistance is achieved Burning effect.

CN119220043AActive Publication Date: 2024-12-31JIANGXI PLASTIC HIGH-TECH MATERIALS CO LTD

Patent Information

Application Number
CN202411720387.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2024-12-31
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing TPE composite materials produce a large amount of thick smoke and toxic gases during combustion, which poses safety risks, and the flame retardant effect of the flame retardant is not ideal.

Method used

A new flame retardant is adopted, which consists of halogen-free flame retardant elements such as nitrogen, phosphorus, silicon and magnesium hydroxide, and is prepared through specific chemical reactions and catalytic steps to form an efficient flame retardant and smoke suppression effect. Organic-inorganic co-effect flame retardant and chemically react with other raw materials in TPE composite materials to improve flame retardant performance.

Benefits of technology

It realizes the efficient flame retardant, low smoke output and low harmfulness of TPE composite materials during combustion, ensuring the safety of the material and the long-lasting and stable flame retardant effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a low-smoke flame-retardant TPE composite material and a preparation method thereof, and belongs to the technical field of high polymer materials. The low-smoke flame-retardant TPE composite material comprises the following raw materials: 80 to 90 parts of SEBS, 60 to 70 parts of white mineral oil, 40 to 50 parts of polypropylene, 40 to 50 parts of a flame retardant, 30 to 40 parts of polyethylene, 20 to 30 parts of an elastomer, 15 to 30 parts of polyphenyl ether, 15 to 25 parts of SBS, 5 to 10 parts of a lubricant, 3 to 5 parts of an antioxidant and 0.2 to 1.2 parts of a vulcanizing agent. The flame retardant is an organic-inorganic synergistic flame retardant and contains rich halogen-free flame-retardant elements such as nitrogen, phosphorus, silicon and magnesium hydroxide, and chemical action exists between the flame retardant and matrix resin, so that the flame retardant can exist in the TPE composite material for a long time and fully exert self-action; therefore, the TPE composite material disclosed by the invention has efficient, safe, stable and lasting flame-retardant and smoke-suppressing effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer materials, and in particular, relates to a low-smoke flame-retardant TPE composite material and a preparation method thereof. Background Art

[0002] Thermoplastic elastomer (TPE) is a material that has the high elasticity, high strength, and high resilience of rubber, and can be processed by injection molding. TPE is environmentally friendly, non-toxic, safe, has a wide range of hardness, excellent colorability, soft touch, weather resistance, fatigue resistance, and temperature resistance. Therefore, as a new type of multifunctional environmentally friendly material, TPE has a very broad application market, such as home appliances, sporting goods, automotive materials, medical equipment, construction industry, and shoemaking industry.

[0003] At present, TPE composite materials are generally prepared from thermoplastic elastomer hydrogenated styrene-butadiene-styrene block copolymer (SEBS), triblock copolymer (SBS) with styrene and butadiene as monomers, thermoplastic plastic polypropylene (PP) and some suitable fillers as raw materials. SEBS / PP type thermoplastic elastomer has both high elasticity of rubber and plasticity of plastic, and has excellent mechanical properties, high and low temperature resistance, weather resistance and flexibility. However, this type of material contains a large amount of white oil plasticizer, white oil has a low ignition point, and SEBS has a large molecular weight, which makes the material very easy to burn and poses a safety hazard. However, the existing ordinary flame-retardant TPE materials generally use decabromodiphenylethane and antimony trioxide flame retardants compounded in a certain proportion. Although they can achieve good flame retardant effects, this type of flame retardant will produce thick smoke and toxic gases during the flame retardant process, which is harmful to the environment and health. Therefore, it is urgent to design and prepare an efficient and safe low-smoke flame-retardant TPE composite material to meet market demand. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a low-smoke flame-retardant TPE composite material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A low-smoke flame-retardant TPE composite material comprises the following raw materials in parts by weight: 80-90 parts of SEBS, 60-70 parts of white mineral oil, 40-50 parts of polypropylene, 40-50 parts of flame retardant, 30-40 parts of polyethylene, 20-30 parts of elastomer, 15-30 parts of polyphenylene ether, 15-25 parts of SBS, 5-10 parts of lubricant, 3-5 parts of antioxidant and 0.2-1.2 parts of vulcanizing agent.

[0006] Furthermore, the flame retardant is prepared by the following steps: S1. Under nitrogen protection, add flame retardant FRC-2 (3-[(hydroxymethyl)amino]-3-oxopropylphosphonic acid-dimethyl ester), 10wt% sodium hydroxide solution and chloroform into a dry three-necked flask, stir evenly and heat to 60°C, then slowly add epichlorohydrin in a constant pressure dropping funnel into the flask, keep warm at 60°C for 5h after the addition, cool to room temperature after the reaction, and distill under reduced pressure to obtain intermediate 1; the amount ratio of flame retardant FRC-2 to epichlorohydrin is 19.3mL:7mL; The molar ratio of flame retardant FRC-2 and epichlorohydrin is controlled to be 1.2-1.3:1, and then flame retardant FRC-2 and epichlorohydrin undergo a ring-opening reaction under heating and base catalysis. The reaction process is as follows:

[0007] S2. Blow nitrogen through a dry three-necked flask for 30 minutes to expel air and moisture from the flask, then add 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, triethylamine and DMSO (dimethyl sulfoxide), mix well and heat to 70°C, then slowly add a mixed solution of intermediate 1 and DMSO, stir at 70°C for 4 hours, cool to room temperature after the reaction, and then distill under reduced pressure to obtain intermediate 2; the dosage ratio of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, intermediate 1, triethylamine and DMSO is 23.4mL:24.3g:15.6mL:180mL; Triethylamine is used as an acid binding agent to control the molar ratio of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to intermediate 1 to be 1.05-1.1:1. Under heating, -NH2 of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and -Cl of intermediate 1 undergo nucleophilic substitution reaction. The reaction process is shown below:

[0008] S3, blow nitrogen gas through a dry three-necked flask for 30 minutes to expel air and moisture from the flask, then add trimethylolpropane trimethacrylate, DBU (1,8-diazobisspiro[5.4.0]undec-7-ene) and DMSO, stir evenly and heat to 60°C, then slowly add a mixed solution of intermediate 2 and DMSO, stir at 60°C for 48 hours after the addition is complete, cool to room temperature after the reaction is complete, distill under reduced pressure, purify by column chromatography (the eluent is a mixed solvent of benzene and ether, the volume ratio of benzene to ether is 6:4), and distill under reduced pressure to obtain intermediate 3; the amount ratio of intermediate 2, trimethylolpropane trimethacrylate, DBU and DMSO is 41.8 g:23.9 mL:2.2 mL:200 mL; Under the catalytic action of DBU, the molar ratio of intermediate 2 and trimethylolpropane trimethacrylate is controlled to be 1.05-1.1:1, and intermediate 2 and trimethylolpropane trimethacrylate undergo Michael addition reaction. The reaction process is as follows:

[0009] S4, blow nitrogen gas into a dry three-necked flask for 30 minutes to expel air and moisture in the flask, then add intermediate 3, DMAP (4-dimethylaminopyridine) and DMF (N,N-dimethylformamide), stir and heat to 50°C, then add a mixed solution of maleic anhydride and DMF, react at 50°C for 12 hours, and after the reaction is completed, distill under reduced pressure, purify by column chromatography (the eluent is a mixed solution of chloroform and ether, and the volume ratio of chloroform and ether is 8:2), and distill under reduced pressure to obtain intermediate 4; the amount ratio of intermediate 3, maleic anhydride, DMAP and DMF is 64.3g:6.9g:0.33g:240mL; Under the catalytic action of DMAP, the molar ratio of intermediate 3 to maleic anhydride is controlled to be 1.05-1.1:1, and then intermediate 3 and maleic anhydride undergo esterification reaction. The reaction process is as follows:

[0010] S5. Under nitrogen protection, add intermediate 4, magnesium hydroxide and DMF into a three-necked flask, mix thoroughly and then slowly add concentrated sulfuric acid. After the addition is complete, heat to 110°C and keep warm for 5 hours. After the reaction is completed, cool to room temperature, filter, wash with deionized water until the filtrate is neutral, and dry at 100°C for 12 hours to obtain a flame retardant; the mass ratio of magnesium hydroxide to intermediate 4 is 9:1.

[0011] Under the catalytic action of concentrated sulfuric acid, the abundant hydroxyl groups on the surface of magnesium hydroxide react with the carboxyl groups on the intermediate 4 to undergo an esterification reaction, and then organic groups are grafted onto the surface of magnesium hydroxide to form a flame retardant, which greatly reduces the surface energy of magnesium hydroxide and greatly increases the compatibility between magnesium hydroxide and the other raw materials in the TPE composite material. The dispersibility of magnesium hydroxide is also greatly improved, and magnesium hydroxide can fully play its role. The reaction process is as follows:

[0012] The flame retardant of the invention contains abundant halogen-free flame retardant elements such as nitrogen, phosphorus, silicon and magnesium hydroxide, and belongs to an organic-inorganic synergistic flame retardant with high efficiency and safety.

[0013] The magnesium hydroxide in the flame retardant is not only flame retardant, but the active MgO generated when it decomposes under heat has not only flame retardant effect but also smoke suppression effect.

[0014] The organic phosphorus in the flame retardant decomposes to generate phosphorus oxygen-containing acids, which can promote the formation of a carbon layer on the substrate. A large amount of carbon layer plays a role in blocking the flow of combustible gases and heat, thereby achieving a flame retardant effect; under the action of nitrogen, the carbon layer formed on the surface of the substrate will expand and foam to form a porous foam structure. The expanded porous foam-like carbon layer will further block the process of heat and oxygen exchange between the substrate and the outside world, further enhancing the flame retardant effect. At the same time, the flame retardant releases a large amount of non-combustible gases such as H2O, NH3, CO2, NO2, etc. during the combustion process, which can dilute the concentration of combustible gases and delay the spread of flames; silicon generates an inorganic thermal insulation protective layer containing -Si-O bonds and -Si-C- bonds during combustion, which not only prevents the decomposition products generated by combustion from escaping, but also inhibits the thermal decomposition of the substrate, achieving the purpose of high flame retardancy, low smoke emission and low harmfulness.

[0015] The flame retardant also contains multiple carbon-carbon double bonds, which can react chemically with the unreacted carbon-carbon double bonds at the ends of polypropylene and polyethylene and the carbon-carbon double bonds on SBS under the action of the vulcanizing agent, so that the flame retardant can stably exist in the TPE composite material. This chemical reaction also further promotes the dispersion of the flame retardant, so that the flame retardant can fully play its role and give the TPE composite material efficient, safe and long-lasting flame retardant and smoke suppression effects.

[0016] Furthermore, the elastomer is one or more of ethylene-octene copolymer, ethylene-octene block copolymer, and styrene elastomer.

[0017] Furthermore, the lubricant is one or more of polyethylene wax, erucamide, dimethyl silicone oil, zinc stearate, calcium stearate, and magnesium stearate.

[0018] Furthermore, the antioxidant is one or more of antioxidant 1010, antioxidant 1076, antioxidant 1098, antioxidant 168, antioxidant 626, and antioxidant 412S.

[0019] Furthermore, the vulcanizing agent is one or more of tert-butyl peroxy isopropyl formate, diisopropyl peroxide, 2,5-dimethyl-2,5-di(tert-butyl peroxy)hexane, and di-tert-butyl peroxide.

[0020] A method for preparing a low-smoke flame-retardant TPE composite material comprises the following steps: Weigh each raw material by weight, add SEBS, SBS, polypropylene and white mineral oil into a high-speed mixer, mix evenly at 90°C, add a vulcanizing agent after cooling, stir evenly, put into a twin-screw extruder for melt blending and cross-linking, water-cooled strand cutting and pelletizing to obtain a cross-linked base material, add the cross-linked base material, elastomer, polyethylene, polyphenylene ether, flame retardant, antioxidant and lubricant into the high-speed mixer in sequence, stir evenly again, put into a twin-screw extruder for melt blending and pelletizing, water-cooled strand cutting and pelletizing to obtain a low-smoke flame-retardant TPE composite material.

[0021] Beneficial effects of the present invention: The flame retardant of the present invention is an organic-inorganic synergistic flame retardant, which is rich in halogen-free flame retardant elements such as nitrogen, phosphorus, silicon and magnesium hydroxide, and there is a chemical reaction between the flame retardant and the matrix resin. Therefore, the flame retardant can exist in the TPE composite material for a long time and give full play to its own role, and thus the TPE composite material of the present invention has efficient, safe, stable and long-lasting flame retardant and smoke suppression effects. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Example 1: Preparation of flame retardant, the specific steps are as follows: S1. Under nitrogen protection, add 19.3 mL of flame retardant FRC-2, 38 mL of 10 wt% sodium hydroxide solution and 180 mL of chloroform into a 500 mL dry three-necked flask, stir evenly and heat to 60°C, then slowly add 7 mL of epichlorohydrin in a constant pressure dropping funnel into the flask, keep warm at 60°C for 5 h after the addition, cool to room temperature after the reaction, and distill under reduced pressure to obtain intermediate 1; S2, nitrogen was blown into a 500 mL dry three-necked flask for 30 min to expel air and moisture in the flask, then 23.4 mL of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 15.6 mL of triethylamine and 100 mL of DMSO were added, mixed evenly and heated to 70°C, then 24.3 g of a mixed solution of intermediate 1 and 80 mL of DMSO were slowly added, stirred at 70°C for 4 h, cooled to room temperature after the reaction was completed, and then distilled under reduced pressure to obtain intermediate 2; S3, nitrogen was blown into a 500 mL dry three-necked flask for 30 min to expel air and moisture in the flask, and then 23.9 mL of trimethylolpropane trimethacrylate, 2.2 mL of DBU and 100 mL of DMSO were added, stirred evenly and then heated to 60°C, and then 41.8 g of a mixed solution of intermediate 2 and 100 mL of DMSO were slowly added, and after the addition was completed, the mixture was stirred at 60°C for 48 h. After the reaction was completed, the mixture was cooled to room temperature, distilled under reduced pressure, purified by column chromatography (the eluent was a mixed solvent of benzene and ether, and the volume ratio of benzene and ether was 6:4), and distilled under reduced pressure to obtain intermediate 3; S4, nitrogen was blown into a 500 mL dry three-necked flask for 30 min to expel air and moisture in the flask, and then 64.3 g of intermediate 3, 0.33 g of DMAP and 200 mL of DMF were added, the mixture was heated to 50°C with stirring, and then a mixed solution of 6.9 g of maleic anhydride and 40 mL of DMF was added, and the mixture was reacted at 50°C for 12 h. After the reaction was completed, it was distilled under reduced pressure, purified by column chromatography (the eluent was a mixed solution of chloroform and ether, and the volume ratio of chloroform and ether was 8:2), and distilled under reduced pressure to obtain intermediate 4; S5. Under nitrogen protection, add 5 g of intermediate 4, 45 g of magnesium hydroxide and 220 mL of DMF into a 500 mL three-necked flask, mix thoroughly and then slowly add 0.17 mL of concentrated sulfuric acid. After the addition is complete, heat to 110°C and keep warm for 5 hours. After the reaction is completed, cool to room temperature, filter, wash with deionized water until the filtrate is neutral, and dry at 100°C for 12 hours to obtain a flame retardant.

[0024] Example 2: Preparation of TPE composite material, the specific steps are as follows: Weigh each raw material by weight, add 80 parts of SEBS, 15 parts of SBS, 40 parts of polypropylene and 60 parts of white mineral oil into a high-speed mixer, mix evenly at 90°C, add 0.2 parts of tert-butyl peroxy isopropyl formate after cooling, stir evenly and put into a twin-screw extruder for melt blending and cross-linking, water-cooled and drawn into pellets to obtain a cross-linked base material, add the cross-linked base material, 20 parts of ethylene-octene copolymer, 30 parts of polyethylene, 15 parts of polyphenylene ether, 40 parts of the flame retardant prepared in Example 1, 1 part of antioxidant 1010, 2 parts of antioxidant 168, 2 parts of polyethylene wax and 3 parts of zinc stearate into a high-speed mixer in sequence, stir evenly again and put into a twin-screw extruder for melt blending and pelletizing, water-cooled and drawn into pellets to obtain a TPE composite material.

[0025] Example 3: Preparation of TPE composite material, the specific steps are as follows: Weigh each raw material by weight, add 86 parts of SEBS, 20 parts of SBS, 45 parts of polypropylene and 67 parts of white mineral oil into a high-speed mixer, mix evenly at 90°C, add 1 part of diisopropylbenzene peroxide after cooling, stir evenly and put it into a twin-screw extruder for melt blending and cross-linking, water-cooled strand cutting and pelletizing to obtain a cross-linked base material, add the cross-linked base material, 26 parts of styrene elastomer, 35 parts of polyethylene, 26 parts of polyphenylene ether, 45 parts of the flame retardant prepared in Example 1, 2 parts of antioxidant 1076, 2 parts of antioxidant 626, 3 parts of erucamide and 4 parts of dimethyl silicone oil into the high-speed mixer in sequence, stir evenly again and put it into a twin-screw extruder for melt blending and pelletizing, water-cooled strand cutting and pelletizing to obtain a TPE composite material.

[0026] Example 4: Preparation of TPE composite material, the specific steps are as follows: Weigh each raw material by weight, add 90 parts of SEBS, 25 parts of SBS, 50 parts of polypropylene and 70 parts of white mineral oil into a high-speed mixer, mix evenly at 90°C, add 0.6 parts of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and 0.6 parts of di-tert-butyl peroxide after cooling, stir evenly and put into a twin-screw extruder for melt blending and cross-linking, water-cooled stranding and pelletizing to obtain a cross-linked base material, the cross-linked base material, 30 parts of ethylene-octene block copolymer, 40 parts of polyethylene, 30 parts of polyphenylene ether, 50 parts of the flame retardant prepared in Example 1, 2 parts of antioxidant 1098, 2 parts of antioxidant 626, 1 part of antioxidant 412S, 5 parts of polyethylene wax and 5 parts of magnesium stearate are sequentially added into a high-speed mixer, stirred evenly again and put into a twin-screw extruder for melt blending and pelletizing, water-cooled stranding and pelletizing to obtain a TPE composite material.

[0027] Comparative Example 1: Preparation of TPE composite material, the specific steps are as follows: The remaining steps remained unchanged, except that the flame retardant in Example 2 was replaced by 36 parts of untreated magnesium hydroxide and 4 parts of ammonium polyphosphate, thereby preparing a TPE composite material.

[0028] Comparative Example 2: Preparation of TPE composite material, the specific steps are as follows: The remaining steps remain unchanged, and only the flame retardant in Example 2 is removed, thereby preparing a TPE composite material.

[0029] Performance test: The TPE composite materials of Examples 2-4 and Comparative Examples 1-2 were made into corresponding samples according to different standards, and the limiting oxygen index test was carried out according to GB / T 2406.1-2008, the flame retardant grade test was carried out according to GB / T 2408-2008, and the smoke density test was carried out according to GB / T 8323. The test results are shown in Table 1 below:

[0030] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0031] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A low-smoke flame-retardant TPE composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 80-90 parts of SEBS, 60-70 parts of white mineral oil, 40-50 parts of polypropylene, 40-50 parts of flame retardant, 30-40 parts of polyethylene, 20-30 parts of elastomer, 15-30 parts of polyphenylene ether, 15-25 parts of SBS, 5-10 parts of lubricant, 3-5 parts of antioxidant, and 0.2-1.2 parts of vulcanizing agent; Wherein, the flame retardant is prepared by the following steps: S1. Add flame retardant FRC-2, 10 wt% sodium hydroxide solution and chloroform into a flask under nitrogen protection, stir and heat to 60°C, add epichlorohydrin, react at 60°C for 5h, cool, and distill under reduced pressure to obtain intermediate 1; S2, after nitrogen blowing into the flask, add 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, triethylamine and DMSO, mix and heat to 70°C, add intermediate 1 and DMSO, react at 70°C for 4h, cool, and distill under reduced pressure to obtain intermediate 2; S3, after nitrogen blowing into the flask, add trimethylolpropane trimethacrylate, DBU and DMSO, stir and heat to 60°C, add intermediate 2 and DMSO, react at 60°C for 48h, cool, distill under reduced pressure, purify by column chromatography, and distill under reduced pressure to obtain intermediate 3; S4, after nitrogen blowing into the flask, add intermediate 3, DMAP and DMF, stir and heat to 50°C, add maleic anhydride and DMF, react at 50°C for 12h, distill under reduced pressure, purify by column chromatography, and distill under reduced pressure to obtain intermediate 4; S5. Under nitrogen protection, add intermediate 4, magnesium hydroxide and DMF into a flask, add concentrated sulfuric acid after mixing, react at 110° C. for 5 h, cool, filter, wash and dry to obtain a flame retardant.

2. The low-smoke flame-retardant TPE composite material according to claim 1, characterized in that: The dosage ratio of flame retardant FRC-2 and epichlorohydrin in step S1 is 19.3mL:7mL; the dosage ratio of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, intermediate 1, triethylamine and DMSO in step S2 is 23.4mL:24.3g:15.6mL:180mL; the dosage ratio of intermediate 2, trimethylolpropane trimethacrylate, DBU and DMSO in step S3 is 41.8g:23.9mL:2.2mL:200mL; the dosage ratio of intermediate 3, maleic anhydride, DMAP and DMF in step S4 is 64.3g:6.9g:0.33g:240mL; the mass ratio of magnesium hydroxide and intermediate 4 in step S5 is 9:

1.

3. The low-smoke flame-retardant TPE composite material according to claim 1, characterized in that: The elastomer is one or more of ethylene-octene copolymer, ethylene-octene block copolymer and styrene elastomer.

4. The low-smoke flame-retardant TPE composite material according to claim 1, characterized in that: The lubricant is one or more of polyethylene wax, erucamide, dimethyl silicone oil, zinc stearate, calcium stearate, and magnesium stearate.

5. The low-smoke flame-retardant TPE composite material according to claim 1, characterized in that: The antioxidant is one or more of antioxidant 1010, antioxidant 1076, antioxidant 1098, antioxidant 168, antioxidant 626, and antioxidant 412S.

6. The low-smoke flame-retardant TPE composite material according to claim 1, characterized in that: The vulcanizing agent is one or more of tert-butyl peroxy isopropyl formate, dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butyl peroxy)hexane, and di-tert-butyl peroxide.

7. The method for preparing a low-smoke flame-retardant TPE composite material according to claim 1, characterized in that: The steps include: Weigh each raw material by weight, add SEBS, SBS, polypropylene and white mineral oil into a high-speed mixer, mix at 90°C, add a vulcanizer after cooling, stir, put into a twin-screw extruder for melt blending and cross-linking, water-cooled and pelletized to obtain a cross-linked base material, add the cross-linked base material, elastomer, polyethylene, polyphenylene ether, flame retardant, antioxidant and lubricant into the high-speed mixer in sequence, stir again, put into a twin-screw extruder for melt blending and pelletizing, water-cooled and pelletized to obtain a low-smoke flame-retardant TPE composite material.

Citation Information

Patent Citations

  • Crosslinked halogen-free flame-retardant TPE material and preparation method thereof

    CN115991925A

  • Anti-aging halogen-free flame-retardant cable material and preparation method thereof

    CN118546452A

  • High-performance low-temperature curing powder coating and preparation method thereof

    CN118562344A

  • High-performance modified PET culture medium bottle and preparation method thereof

    CN118638397A

  • Low-smoke flame-retardant power cable and preparation process thereof

    CN118866449A

Cited By

  • High-temperature-resistant flame-retardant nylon composite material and preparation method thereof

    CN120607809A